High School Student’s Perceptions of Augmented Reality Technology in Animaxtion Art Exhibition - Pratama, Tito Ari; Pranindyasari, Chelsia (Universitas Ciputra, 2025)
This study investigates high school students’ perceptions of Augmented Reality (AR) technology in the Animaxtion art exhibition organized by Multimedia Nusantara Polytechnic. AR has transformed animated art exhibitions by offering interactive and immersive experiences, yet its acceptance among young visitors remains underexplored. Employing a quantitative approach based on the Technology Acceptance Model (TAM), data were collected through surveys distributed to exhibition visitors. The study examined perceived usefulness and ease of use as factors influencing visitors’ intention to engage with AR-based artworks. Descriptive and regression analyses revealed that both factors significantly affected visitor acceptance, with most respondents perceiving AR as enjoyable and helpful for appreciating animation. However, several participants reported hesitation due to limited device compatibility and inconsistent performance. The findings highlight AR’s potential as an engaging educational and artistic medium while emphasizing the need for improved implementation strategies. This research contributes insights into design and technology integration within interactive exhibitions.